The Routledge companion to digital media and children - Green, Lelia; Holloway, Donell; Stevenson, Kylie; Leaver, Tama (New York : Routledge, 2021)
"This companion presents the newest research in this important area, showcasing the huge diversity in children's relationships with digital media around the globe, and exploring the benefits, challenges, history, and emerging developments in the field. Children are finding novel ways to express their passions and priorities through innovative uses of digital communication tools. This collection investigates and critiques the dynamism of children's lives online with contributions fielding both global and hyper-local issues, and bridging the wide spectrum of connected media created for and by children. From education to children's rights to cyberbullying and youth in challenging circumstances, the interdisciplinary approach ensures a careful, nuanced, multi-dimensional exploration of children's relationships with digital media. Featuring a highly international range of case studies, perspectives, and socio-cultural contexts, The Routledge Companion to Digital Media and Children is the perfect reference tool for students and researchers of media and communication, family and technology studies, psychology, education, anthropology, and sociology, as well as interested teachers, policy makers, and parents"--
Includes bibliographical references and index.
Keywords: Mass media and children